Wnt Signalling Promotes Actin Dynamics during Axon Remodelling through the Actin-Binding Protein Eps8. - Eleanna Stamatakou; Monica Hoyos-Flight; Patricia C Salinas (PLoS ONE)
Upon arrival at their synaptic targets, axons slow down their growth and extensively remodel before the assembly of presynaptic boutons. Wnt proteins are target-derived secreted factors that promote axonal remodelling and synaptic assembly. In the developing spinal cord, Wnts secreted by motor neurons promote axonal remodelling of NT-3 responsive dorsal root ganglia neurons. Axon remodelling induced by Wnts is characterised by growth cone pausing and enlargement, processes that depend on the re-organisation of microtubules. However, the contribution of the actin cytoskeleton has remained unexplored. Here, we demonstrate that Wnt3a regulates the actin cytoskeleton by rapidly inducing F-actin accumulation in growth cones from rodent DRG neurons through the scaffold protein Dishevelled-1 (Dvl1) and the serine-threonine kinase Gsk3β. Importantly, these changes in actin cytoskeleton occurs before enlargement of the growth cones is evident. Time-lapse imaging shows that Wnt3a increases lamellar protrusion and filopodia velocity. In addition, pharmacological inhibition of actin assembly demonstrates that Wnt3a increases actin dynamics. Through a yeast-two hybrid screen, we identified the actin-binding protein Eps8 as a direct interactor of Dvl1, a scaffold protein crucial for the Wnt signalling pathway. Gain of function of Eps8 mimics Wnt-mediated axon remodelling, whereas Eps8 silencing blocks the axon remodelling activity of Wnt3a. Importantly, blockade of the Dvl1-Eps8 interaction completely abolishes Wnt3a-mediated axonal remodelling. These findings demonstrate a novel role for Wnt-Dvl1 signalling through Eps8 in the regulation of axonal remodeling.